Can seniors be trendy? Elderly people in pop culture - Korczewska, Karolina (Instytut Socjologii Uniwersytet Wrocławski, 2014)
This paper is based on media releases and describes aspects of the modern lifestyle of senior citizens. It promotes gerontological pedagogy in the context of positive attitudes to ageing.
Keywords: elderly people; modern lifestyle of senior citizens; positive ageing; old age in popular culture